Three-dimensional velocity structure model for hypocenter determination in and around the Japanese Islands - Akio Katsumata; Takahito Nishimiya (Earth, Planets and Space)
Abstract We constructed a three-dimensional (3D) velocity structure model to determine hypocenters in and around the Japanese Islands. Whereas one-dimensional (1D) models are good approximations in many cases, the estimated focal depth distribution of hypocenters tends to be affected by the assumed velocity structure model more than the horizontal distribution. A 3D velocity structure was estimated to obtain more accurate hypocenter locations than those based on a 1D model with a tomographic analysis. In the tomography, sequential analysis from shallower to deeper layers was adopted to avoid correlation between shallower and deeper layers. High velocity in subducting slabs was introduced as the initial model for the tomography. We compared estimated hypocenter distributions with those obtained by temporal dense networks. Using the estimated velocity structure, we obtained hypocenter distributions more consistent with those of temporal dense networks. For shallow inland earthquakes, the velocity difference affects focal depths considerably. The focal depth differences between 1D and 3D models reached several kilometers for inland earthquakes. In some cases, this focal depth difference makes it difficult to assume earthquake faults from aftershock distributions. For offshore areas where stations above the source area are not available, poor depth resolution often makes it difficult to get images of the earthquake faults. The estimated velocity structure helped to obtain fault geometries for some offshore events. Deep hypocenters far from the observation network exhibit systematic deviation from their real locations because of the high velocity of the subducting slabs. The ISC-EHB hypocenters have relatively high accuracy because they were estimated with depth phases from a global network. Locations in the ISC-EHB Bulletin were referred to as reliable locations in the tomography. Using the estimated velocity structure, the hypocenters estimated with regional network data became more consistent with the ISC-EHB Bulletin. Graphical Abstract